2015
DOI: 10.4293/jsls.2014.00205
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Follow-Up by a Midlevel Provider After Laparoscopic Inguinal Hernia Repair Instead of Face-to-Face Clinic Visit

Abstract: Background and Objectives:The need for more cost- and time-efficient provision of medical care has prompted an interest in remote or telehealth approaches to delivery of health care. We present a study examining the feasibility and outcomes of implementation of a telephone follow-up program for laparoscopic inguinal hernia repair.Methods:This is a retrospective review of consecutive patients who prospectively agreed to undergo telephone follow-up after laparoscopic inguinal hernia repair instead of standard fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 9 publications
1
45
0
1
Order By: Relevance
“…Telemedicine was used during the postoperative period on 3 primary timetables: for scheduled follow-up, 4554 for routine and ongoing monitoring, 43,44,51,55,58 or for management of issues as they arose. 56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine was used during the postoperative period on 3 primary timetables: for scheduled follow-up, 4554 for routine and ongoing monitoring, 43,44,51,55,58 or for management of issues as they arose. 56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 Seven studies examined the potential for replacing follow-up clinic visits with a telephone call 47,54 or an online videoconference, either from the patient’s home 45,48,49 or from an affiliated remote clinic site. 50,52,53 Among the studies using telemedicine for ongoing monitoring, patients’ reported symptoms were collected either by automated telephone survey 43 or videophone with live patient interviews.…”
Section: Resultsmentioning
confidence: 99%
“…In addition patients will receive a telephone call 2 weeks after surgery to inform them about any test results. Various studies already have proven that telephone follow-up is feasible and effective after the type of surgical procedures which are included in this study [26-28]. The telehealth follow-up aims to replace the standard single postoperative consultation in the outpatient clinic to increase access to care, reduce patient uncertainties and fear related to the recovery process, reduce costs and workload, and meet patient preferences of care during out-of-office hours [29,30].…”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35][36][37] Still others have eliminated both "hands-on" and visual assessments, using telephone to follow-up adults after laparoscopic cholecystectomy and inguinal hernia repair as well as a variety of minor pediatric general surgical procedures. [38][39][40] Both video and telephone-based care are limited in that they must be performed in a synchronous fashion, with both patient and surgeon available concurrently to participate in follow-up. Telephone assessments are further limited in their inability to visually assess the surgical site.…”
Section: Discussionmentioning
confidence: 99%